Nickel-catalyzed synthesis of 1,1-diborylalkanes from terminal alkenes - Lei Li (Nature Portfolio, 2017)
1,1-diborylalkanes are useful building blocks in synthetic chemistry. Here, the authors present a highly chemo- and regioselective Ni-catalyzed reaction for the synthesis of 1,1-diborylalkanes from a wide variety of readily available terminal alkenes.